2019
DOI: 10.1016/j.radphyschem.2019.108409
|View full text |Cite
|
Sign up to set email alerts
|

Alpha radiolysis of DOTA ligand in aqueous solutions with helium ion beams

Abstract: Alpha irradiation of DOTA ligand in pure water with helium ion beam was studied.• As DOTA concentration in water increases, H2O2 formation decreases.• Whereas molecular hydrogen (H2) and carbon dioxide (CO2) formation increases.• DOTA degradation products were identified by ESI-MS.• A degradation scheme for the DOTA ligand is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
2
6
0
Order By: Relevance
“…A decrease in signal intensity is observed upon irradiation, which was also reported by Fiegel et al 36 They observed that the higher the concentration of DOTA in solution, the higher the hydrogen yields and attributed the decrease in NMR signal intensity to the degradation of DOTA through hydrogen abstraction leading to the formation of molecular hydrogen H 2 . 36 At 20 and 30 kGy, DOTA keeps degrading. This results in a decrease in intensity and an increasing shift of the NMR signals.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…A decrease in signal intensity is observed upon irradiation, which was also reported by Fiegel et al 36 They observed that the higher the concentration of DOTA in solution, the higher the hydrogen yields and attributed the decrease in NMR signal intensity to the degradation of DOTA through hydrogen abstraction leading to the formation of molecular hydrogen H 2 . 36 At 20 and 30 kGy, DOTA keeps degrading. This results in a decrease in intensity and an increasing shift of the NMR signals.…”
Section: Resultssupporting
confidence: 77%
“…Our experimental results and previous work 36 show that cyclen bonds of DOTA are not subjected to radiolysis, while the acetate arms can be broken. Therefore, BDEs were calculated only for the bonds belonging to the acetate arms.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…are being studied as a promising cure for cancer 3–6 . Despite the different fields of application both of these areas are connected by the chemistry of aqueous solutions under irradiation 7–11 . Experimental methods require special laboratory conditions with the use of sources of ionizing radiation (accelerators, gamma‐chambers, and nuclear reactors).…”
Section: Introductionmentioning
confidence: 99%